Effectiveness of a Joint Police and Social Services Response to Elder Abuse in Manhattan (New York City), New York, 1996-1997 - Davis, Robert C. ([Verlag nicht ermittelbar], 2001)
This project consisted of an evaluation of an elder abuse program run by the New York Police Department and Victim Services Research. The focus of the study was domestic elder abuse, which generally refers to any of several forms of maltreatment, physical abuse, sexual abuse, psychological abuse, neglect, and/or financial exploitation of an older person. The program, conducted in New York City public housing, had two complementary parts. First, public housing projects in Manhattan were assigned to one of two levels of public education (i.e., to receive or not to receive educational materials about elder abuse). Once the public education treatment had been implemented, 403 older adult residents of the housing projects who reported elder abuse to the police during the next ten months were assigned to one of two levels of follow-up to the initial police response (i.e., to receive or not to receive a home visit) as the second part of the project. The home visit intervention consisted of a strong law enforcement response designed to prevent repeat incidents of elder abuse. A team from the Domestic Violence Intervention and Education Program (DVIEP), consisting of a police officer and a social worker, followed up on domestic violence complaints with a home visit within a few days of the initial patrol response. Victims were interviewed about new victimizations following the intervention on three occasions: six weeks after the trigger incident, six months after the trigger incident, and twelve months after the trigger incident. Interviews at the three time points were identical except for the omission of background information on the second and third interviews. Demographic data collected during the first interview included age, gender, ethnicity, education, employment, income, legal relationship with abuser, living situation, number of people in the household, and health. For each time point, data provide measures of physical, psychological, and financial abuse, knowledge of elder abuse, knowledge and use of social services, satisfaction with the police, assessment of service delivery, and self-esteem and well-being. The DVIEP databases maintained on households at each of the three participating Police Service Areas (PSAs) were searched to identify new police reports of elder abuse for households in the sample within 12 months following the trigger incident. Variables from the DVIEP databases include age, race, ethnicity, and sex of the victim and the perpetrator, relationship of perpetrator to victim, type of abuse reported, charge, whether an arrest was made, if an order of protection had been obtained, if the order of protection was violated, use of weapons, if the victim had been injured, and if the victim was taken to the hospital. Several time lapse variables between different time points are also provided.